“Producción de pepino (cucumis sativus.) con dos sistemas de tutorado”. - Díaz Ayala, Karina Noemí (2017)
The research was carried out at the Experimental Center "La Playita", of the Technical University of Cotopaxi, in the province of Cotopaxi. (Geographic Location WGS 84: Latitude SO ° 56'27 "Longitude W 79 ° 13'25"), with height of 193 meters above sea level. The following objectives were proposed: To evaluate growth indicators in cucumber plants under two tutorial systems. To determine some production indicators in cucumber plants under two tutorial systems. To assess the feasibility of economic tutorial systems in cucumber. The experimental design used was a Completely Randomized Design (CRA), with two treatments six repetitions plus an absolute witness. The variables which were evaluated: Height of plant, number of fruits, length of fruits, diameter of fruits, weight of fruits, number of damaged fruits, and the percentage of efficiency. The results were: The highest plant was recognized at 15 days with the tutorial treatments with mesh, whit the following values of 24,81 cm, the highest number of fruits was obtained with the tutorial with 6,79, in the length of fruit the greatest value was given with the tutorial using meshes with 27,70 cm, the largest diameter of fruits the tutorial with meshes presented better results with 5,84 centimeters, the tutorial with meshes reached greater weight of fruit with 539,64, the less number of damaged fruits was registered in the tutorial implementing with meshes with 0.67 fruits in poor condition, the highest efficiency was achieved with the tutorial based on meshes, with an efficiency of 90.09%.